COLLABORATIVE GOVERNANCE DALAM PROGRAM KELUARGA BERENCANA DI KABUPATEN KAMPAR TAHUN 2023 - Amalia, Lisa Putri; Febrina, Rury (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Collaborative governance has become an essential need. Involving the government, the private sector, non-governmental organizations, and civil society in the formulation and implementation of family planning policies will ensure a comprehensive and integrated framework. This research has the problem formulation